Transforming Tahfiz Education through Religious Moderation: Curriculum, Content, Teachers, and Evaluation in Indonesian Rumah Tahfiz Al-Qur’an - Rijal Ahmad Rangkuti (Journal of Social Work and Science Education, 2027)
This study examines the transformation of Tahfiz education management in Indonesian Rumah Tahfiz al-Qur'an (RTQs) through the integration of religious moderation values, moving beyond traditional memorization-focused approaches. A qualitative phenomenological approach was employed, combining library research and field research through observations and interviews to analyze four key dimensions of educational transformation. Findings reveal significant transformation in: (1) curriculum design, integrating character building and social attitude development alongside memorization targets; (2) learning content, encompassing Qur'anic memorization, meaning understanding, 'Ulum al-Qur'an studies, and practical value application; (3) teacher qualifications, emphasizing scholarly competence, pedagogical skills, moral integrity, and exemplary conduct; and (4) evaluation systems, comprehensively assessing cognitive, affective, and psychomotor competencies. Religious moderation values national commitment, tolerance, anti-violence, anti-radicalism, and local culture appreciation are internalized through learning processes, habituation, role modeling, and daily practices. This study uniquely documents the institutional evolution of RTQs from memorization-centered centers to holistic Islamic educational institutions integrating religious moderation, an underexplored transformation in Indonesian non-formal Islamic education. Findings offer practical guidance for policymakers and practitioners in designing religious moderation-infused Qur'anic education programs. This research contributes to Islamic educational theory by demonstrating that RTQs are evolving into institutions capable of producing graduates with strong Tahfiz abilities, adequate religious understanding, moderate character, and readiness for pluralistic society.